STRATEGI “S-M-A-R-T” DALAM PENGELOLAAN LITERASI MADRASAH MENUJU GOOD PRACTICE SCHOOL DI MTs PESANTREN TERPADU AL FAUZAN - Naning Maryana, S.Pd. (Madaris: Jurnal Guru Inovatif, 2021)
The “SMART” strategy successfully managing madrasa and achieving the title of Good Practice School in 2016, with various impacts namely, first, the formulation of systematic long-term Madrasa Work Plan or Rencana Kerja Madrasah (RKM Secondly, madrasa actually carry out a model of madrasah management that is literated, especially those involving madrasa’s policies, curriculum, madrasa’s activities and the utilization of madrasa’s infrastructure. Third, in 2014 collaborated with USAID Priority through good learning training, school-based management and community participation. USAID conducted a centralized assessment and the result in 2016 were declared as Good Practice School. Fourth, the teaching and learning process runs more actively. Fifth, there is a change in behaviour of madrasa residents both students and teachers also madrasah employees towards reading interest. Sixth, madrasa become one of the destinations for other school to conduct comparative studies, both school in the district of Lumajang and outside Lumajang regency, even from outside the province. MTs Pesantren Terpadu Al Fauzan received a comparative study visitation from USAID Priority South Sulawesi Cohort 2 and USAID Priority Banyuwangi Cohort 3. The further action after achieving a Good Practice School is to strengthen the program activities in order to support the implementation of the management of literate madrasas, although no further evaluation of the Good Practice School in MTs Pesantren Terpadu Al Fauzan.